An unexpected role of Nogo-A as regulator of tooth enamel formation - Pierfrancesco Pagella; Chai Foong Lai; Laurence Pirenne; Claudio Cantù; Martin E. Schwab; Thimios A. Mitsiadis (Nature Publishing Group, 2024)
Abstract Neurite outgrowth inhibitor A (Nogo-A) is a major player in neural development and regeneration and the target of clinical trials aiming at promoting the regeneration of the central nervous system upon traumatic and ischemic injury. In this work, we investigated the functions of Nogo-A during tooth development to determine its role in dental physiology and pathology. Using immunohistochemistry and in situ hybridization techniques, we showed that Nogo-A is highly expressed in the developing mouse teeth and, most specifically, in the ameloblasts that are responsible for the formation of enamel. Using both Nogo-A knockout and K14-Cre;Nogo-A fl/fl transgenic mice, we showed that Nogo-A deletion in the dental epithelium leads to the formation of defective enamel. This phenotype is associated with overexpression of a set of specific genes involved in ameloblast differentiation and enamel matrix production, such as amelogenin, ameloblastin and enamelin. By characterising the interactome of Nogo-A in the dental epithelium of wild-type and mutant animals, we found that Nogo-A directly interacts with molecules important for regulating gene expression, and its deletion disturbs their cellular localisation. Furthermore, we demonstrated that inhibition of the intracellular, but not cell-surface, Nogo-A is responsible for gene expression modulation in ameloblasts. Taken together, these results reveal an unexpected function for Nogo-A in tooth enamel formation by regulating gene expression and cytodifferentiation events.